How much do they remember? Anatomical knowledge retention in nursing education- a four-year longitudinal study - Narnaware, Yuwaraj; Manwatkar, Sushma (My University, 2024)
The human anatomy is regarded as a cornerstone of health care disciplines and is a pre-requisite for subsequent years of medical, allied health and nursing theory courses and clinical (Young et al., 2016). Numerous studies have expressed concern over students' ability to acquire anatomical knowledge in the first year and successfully transfer, retain, and apply it throughout their program (Doomernik et al., 2017; Narnaware and Neumeier, 2020). This study seeks to determine the overall and system specific anatomy knowledge retention by nursing students over a Bachelor of Science in Nursing (BScN) program at MacEwan University.
Presented September 5-8, 2024, at the International Federation of Association of Anatomists (IFAA), Gwangju, South Jeolla Province, South Korea.
Keywords: human anatomy; healthcare disciplines; allied health and nursing